2009
DOI: 10.1038/sj.bjc.6604861
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study and biomarker analysis of cetuximab combined with modified FOLFOX6 in advanced gastric cancer

Abstract: This prospective study was conducted with the Korean Cancer Study Group to evaluate the efficacy and safety of cetuximab combined with modified FOLFOX6 (mFOLFOX6) as first-line treatment in recurrent or metastatic gastric cancer and to identify potential predictive biomarkers. Patients received cetuximab 400 mg m À2 at week 1 and 250 mg m À2 weekly thereafter until disease progression. Oxaliplatin (100 mg m À2 ) and leucovorin (100 mg m À2) were administered as a 2-h infusion followed by a 46-h continuous infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 34 publications
6
96
2
Order By: Relevance
“…These results are supported by the current study in which the median TTP was found to be 7.6 months. A shorter TTP of median 5.5 months, together with a noteworthy response rate of 50%, was reported in the first cetuximab -chemotherapy study published from East Asia (Han et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by the current study in which the median TTP was found to be 7.6 months. A shorter TTP of median 5.5 months, together with a noteworthy response rate of 50%, was reported in the first cetuximab -chemotherapy study published from East Asia (Han et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of EGFR overexpression reported in previous studies varies from 2 % to 81 %, probably the result of differences in antibodies, scoring systems, and observers [4,21,[24][25][26][27][28][29][30][31][32]. In contrast, the frequency of EGFR gene amplification in gastric cancers is consistently less variable (2-7 %), although most of these studies lacked a sufficiently large number of patients or a detailed EGFR GCN examination [3,5,22,24,26,29,30].…”
Section: Introductionmentioning
confidence: 70%
“…The recent REAL3 (panitumumab) [19] and EXPAND (cetuximab) [20] randomized controlled phase III trials failed to demonstrate the efficacy of the anti-EGFR monoclonal antibodies for treating gastric cancer, presumably because precise patient inclusion criteria were not set for the trials. Several studies suggest that EGFR overexpression or gene amplification may serve as a potential biomarker for the efficacies of anti-EGFR therapies in gastric cancer [9,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The current standard of not testing colorectal tumours for EGFR expression may not apply for other epithelial tumour histologies. It is possible that low serum ligand levels of EGF or TGFa would correlate better with response, as suggested by one study (Han et al, 2009). Recent phase II and III trials have shown that the presence of a K-ras mutation in tumours predicts response to EGFR-targeted therapy (Allegra et al, 2009).…”
Section: Discussionmentioning
confidence: 98%